2002
DOI: 10.1128/mcb.22.18.6611-6626.2002
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-Dependent Subcellular Redistribution of the Transcriptional Coactivator p/CIP

Abstract: The transcriptional coactivator p/CIP is a member of a family of nuclear receptor coactivator/steroid receptor coactivator (NCoA/SRC) proteins that mediate the transcriptional activities of nuclear hormone receptors. We have found that p/CIP is predominantly cytoplasmic in a large proportion of cells in various tissues of the developing mouse and in a number of established cell lines. In mouse embryonic fibroblasts, serum deprivation results in the redistribution of p/CIP to the cytoplasmic compartment and sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 76 publications
(85 reference statements)
3
31
0
3
Order By: Relevance
“…Both AIB1 and AIB1-⌬4 contain the nuclear export sequence that is in the C-terminal half of the proteins (Fig. 1d) (27), so we hypothesized that if we blocked nuclear export then the AIB1-⌬4 protein would accumulate in the nucleus if it is imported into the nucleus. CHO cells were transfected with FLAG AIB1-⌬4 in media with 10% FBS and were either treated with vehicle or leptomycin B.…”
Section: Aib1-⌬4 Is a Predominantly Cytoplasmic Protein That Enters Tmentioning
confidence: 99%
“…Both AIB1 and AIB1-⌬4 contain the nuclear export sequence that is in the C-terminal half of the proteins (Fig. 1d) (27), so we hypothesized that if we blocked nuclear export then the AIB1-⌬4 protein would accumulate in the nucleus if it is imported into the nucleus. CHO cells were transfected with FLAG AIB1-⌬4 in media with 10% FBS and were either treated with vehicle or leptomycin B.…”
Section: Aib1-⌬4 Is a Predominantly Cytoplasmic Protein That Enters Tmentioning
confidence: 99%
“…SRC-1 has been reported to be present in the nucleus [28,29,30], in the cytoplasm [31] or in both compartments [32]. Similar divergent data have been described for SRC-3, ranging from cytoplasmic to diffuse nucleoplasmic or discrete intranuclear foci [33,34]. SRC-2 is essentially localized in the nucleus with both diffuse and focal accumulation although weak expression was also detected in cytoplasm [31,33,35,36].…”
Section: Discussionmentioning
confidence: 59%
“…Recently, nucleocytoplasmic shuttling of p160 coactivators has been reported by several groups (43 -45). Qutob et al (44) showed that p/CIP (mouse TRAM-1) is localized in either the nucleus or cytoplasm, depending on the presence of growth factors in cell culture medium and on the effect of leptomycin B. They demonstrated that cytoplasmic p/CIP associates with tubulin and that an intact microtubule network is required for intracellular shuttling of p/CIP.…”
Section: Discussionmentioning
confidence: 99%